Analysis and design the system for receiving a new student at Islamic institute abdullah faqih ( INKAFA) - Anindya, Nurvina Leila; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Institute of subjects abdullah faqih (INKAFA) is private universities located in kabupaten gresik .As since 2013 until 2015 , this institute increased the number of registered as a candidate new students , so with the this services were to be raised .Therefore , management inkafa issued a policy to do migration from manual processes be process that computerized.Seeing the opportunity that is , the management inkafa requires an analysis and design the system for receiving new students that went into reference in making an application as on inkafa .Therefore , to research is made a analysis and design that can help the entire range of the process of admission to new students.The results of the analysis and design this system produced a document containing analysis problems, operational analysis, analysis of the needs on data, analysis the availability of, analysis capacity, analysis performance, the best thing of analysis, and analysis security, and design system which includes system flow, diagram context, diagram level, data flow diagram level 0 and 1.Design data, ui design, design security and a system design.From the analysis and the design portray a the things needed in building the system for receiving students the necessary new inkafa.Keywords : analysis , design system , the new students